F-Linear - Conceição, Ana C. (2012)
F-Linear is a F-Tool (see http://hdl.handle.net/10400.1/1105), that is, a visual, dynamic, and interactive teaching tool that allow to explore in an innovate fashion some of the main concepts within precalculus and differential calculus at the secondary and university levels (available in the CDF format).